Studi Kasus Tingkat Kebisingan di Kamar Mesin Dan Pemilihan Peredaman - wahyono, maretha (PT Yupin Felicitas Utama, 2025)
This research was conducted to understand the extent to which excessive vibration can affect bearing damage and shaft misalignment in a ship's main engine. Uncontrolled vibration is often a primary cause of damage in machinery systems, particularly in moving or rotating components. In this case study, the approaches used included direct observations and vibration amplitude measurements at several critical points, such as the shaft and bearings. The measurement results indicated that the vibration amplitudes at Bearing 1, Bearing 2, and Shaft B exceeded the allowable standard threshold, indicating significant wear and misalignment. These findings are consistent with previous studies that have shown a strong correlation between increased machine component vibration and a higher risk of failure. Based on this, the study emphasizes the importance of routine vibration monitoring as a preventive measure to detect damage early and avoid more severe operational disruptions. By implementing an effective vibration monitoring system, the reliability of the machinery system can be improved, and the service life of the ship's main engine can be extended.